Water as a critical issue for viticulture in southern Europe: sustainability vs competiveness - Costa, J.M. (2022)
Sourced from the research article “Modern viticulture in southern Europe: vulnerabilities and strategies for adaptation to water scarcity” (Agricultural Water Management, 2016)